LUSPATERCEPT – AN INNOVATIVE APPROACH TO THE TREATMENT OF ANEMIA IN BETA-THALASSEMIA AND MYELODYSPLASTIC SYNDROMES - Dominik Domoń,; Adam Niedziela,; Hanna Wilska,; Dominika Domanowska,; Antoni Liebert,; Natalia Klimek,; Martyna Kaplińska,; Bartosz Rutka,; Karolina Niewczas,; Adrianna Brzozowska, (International Journal of Innovative Technologies in Social Science, 2025)
Ineffective erythropoiesis (IE) is a hallmark of several hematologic disorders, including β-thalassemia and myelodysplastic syndromes (MDS), leading to chronic anemia and transfusion dependence. IE is often driven by disrupted late-stage erythroid maturation, mediated by overactivation of the Smad2/3 signaling pathway within the transforming growth factor-β (TGF-β) superfamily. This review summarizes current evidence on the mechanism of action and clinical efficacy of luspatercept, a novel activin receptor ligand trap that enhances erythroid maturation by inhibiting Smad2/3 signaling. A literature search was conducted using PubMed through February 2025, focusing on clinical trials and mechanistic studies of luspatercept in β-thalassemia and MDS. In β-thalassemia, luspatercept significantly reduced transfusion burden in phase I–III trials. The pivotal BELIEVE study demonstrated that ≥33% transfusion reduction was achieved in a significantly higher proportion of patients receiving luspatercept compared to placebo. In low-risk MDS (LR-MDS), phase II PACE-MDS and phase III COMMANDS trials showed that luspatercept induced erythroid response (HI-E) and transfusion independence (RBC-TI) in a substantial proportion of patients. COMMANDS further revealed that luspatercept outperformed epoetin alfa in achieving ≥12-week RBC-TI and ≥1.5 g/dL hemoglobin increase, regardless of SF3B1 mutation status or baseline erythropoietin levels. Luspatercept presents a promising treatment strategy for IE in β-thalassemia and LR-MDS. Its ability to promote erythropoiesis, reduce transfusion needs, and maintain a favorable safety profile supports its potential as a new standard of care. Ongoing research will help define its role across broader patient populations.